Effect of wave disturbance on the fluid dynamics of the pump turbine in a seawater pumped storage hydroplant - Hu, Jianyong; Wang, Qingbo; Song, Hongge; Mao, Jiahua (Frontiers in Earth Science, 2023)
Comparing with conventional pumped storage hydroplants, seawater pumped storage hydroplants are constructed in complex marine environment. The wave disturbance may affect the safety operation of the pump-turbine in the seawater pumped hydroplant via affect the level of free water surface. To explore the effect of the wave disturbance on the operation of the pump-turbine in seawater pumped storage hydroplant, assuming that the wave disturbance follows a sine function, on the basis of Airy's micro-amplitude wave theory and the comprehensive characteristic curve of a pump-turbine, we use sliding grid technology and the SST k-ω turbulence model to simulate the dynamics of fluid in a full-flow channel. In this study, the unsteady flow field, Q criterion vorticity, relative pressure pulsation amplitude, and frequency of pressure pulsation are analyzed, to determine the internal flow field and pressure pulsation under different wave disturbance conditions and operating loads. The results show that both the pressure pulsation in the pump turbine and its frequency domain is affected by the wave disturbance. In addition, the turbulent flow with large flow rate trends to produce higher relative pressure pulsation under wave disturbance. Due to the large flow rate and strong static and dynamic interference in the vaneless area, the relative amplitude of the pressure pulsation is significantly affected by wave disturbance. Also, the low-frequency pressure pulsation of the draft tube is superimposed with the wave disturbance’s frequency.